Evidence-based case report: effects of exercise-based cardiac rehabilitation in repaired tetralogy of Fallot - Salam, Muhamad Elfitra; Putra, Bima Lesmana (Gaster, 2025)
Background: Several sequelae may persist following corrective surgery for tetralogy of Fallot (ToF), including reduced exercise capacity, compromised vascular and cardiac autonomic function, and diminished quality of life. While exercise-based cardiac rehabilitation is commonly implemented for patients with congenital heart disease, there remains a lack of comprehensive understanding regarding the optimal frequency, intensity, duration, and type of exercise. This evidence-based case report aims to evaluate the effectiveness of physical exercise on exercise capacity and quality of life in patients who have undergone ToF repair. Method: A literature search was conducted in PubMed, Cochrane, and Google Scholar databases in September to December 2024 using keywords "exercise," "cardiac rehabilitation," and "tetralogy of Fallot." Studies were included if they involved human subjects with tetralogy of Fallot, were published in English within the past fifteen years, and provided primary data. Studies were excluded if they were duplicates, had unavailable full texts, were research protocols, or review articles. Results: Six articles met the established inclusion and exclusion criteria. Data extraction revealed that various studies consistently demonstrated significant improvements (p<0.05) in peak oxygen uptake (VO2 peak) and quality of life (QoL), particularly in the mental and social domains. Conclusion: Exercise-based cardiac rehabilitation can be beneficial for patients post-ToF repair. However, it is essential to consider factors such as the duration since corrective surgery, the appropriate dosage of exercise, and the specific types of exercise prescribed.